Elaboración de un stop motion con el fin de desarrollar la estimulación temprana en niños de 2 a 3 años, dirigido a educadores de la Modalidad Creciendo con Nuestros Hijos del Ministerio de Inclusión Económica y Social del Distrito Latacunga - Chicaiza Toabanda, Bolívar Roberto (2017)
The Ministry of Economic and Social Inclusion of the Latacunga District has the program called "Modality Growing with Our Children", this project reaches places far from the canton where pre-school education is developed for children from 2 to 3 years. The problem is that educators do not have audiovisual material to strengthen the process of early stimulation in the area of language, being that they must travel long distances (in transport and on foot), to meet with the children, and in a single time of Approximately 30 minutes; In this space teachers develop early stimulation exercises. Early education provides children, is to develop skills, skills and abilities, so that the proposal to carry out a stop motion that stimulates language development is a significant contribution that opens a space for new research proposals, for the elaboration of the product photography will be the main tool to be used. The research was carried out based on the qualitative-quantitative methodology, obtaining favorable results to produce the audiovisual material product that satisfies the social need, as a support for the "Growing with Our Children" modality.